Author Response: Spontaneous ARIA-like Events in Cerebral Amyloid Angiopathy–Related Inflammation: A Multicenter Prospective Longitudinal Cohort Study. (18th October 2022) - Piazza, Fabrizio; Basso, GianPaolo; Pascarella, Rosario; Carare, Roxana O.; Zedde, Marialuisa
Abstract : We are grateful for the comments on our research, which we believe provides important considerations for future protocols and biomarkers dedicated to the surveillance and management of amyloid-related imaging abnormalities (ARIAs) in clinical practice. 1 ARIAs are emerging as much more complex and frequent phenomena than initially acknowledged. Our data suggest therapy-induced ARIAs are iatrogenic manifestations of the spontaneous ARIAs of cerebral amyloid angiopathy–related inflammation (CAA-ri), an autoimmune encephalopathy syndrome associated with raised anti-Aβ autoantibodies in the CSF. 1